2020
DOI: 10.31616/asj.2020.0122
|View full text |Cite
|
Sign up to set email alerts
|

Advice on Standardized Diagnosis and Treatment for Spinal Diseases during the Coronavirus Disease 2019 Pandemic

Abstract: Coronavirus disease 2019 outbreak started in December 2019 that caused difficulties for clinical work. Practical work experience in our spinal outpatient and emergency department during the COVID-19 pandemic is summarized in this article, with combined evidence-based medical evidence to explore a standardized process of diagnosis and treatment for spinal diseases. Outpatient reservation, continuous screening, triage, and isolation, first consultation accountability system, pandemic reporting system, and onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
5

Year Published

2020
2020
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 14 publications
0
64
0
5
Order By: Relevance
“…The authors designed an algorithm to assess patients, presented in Fig.1. This is in contrast to the previous review, "Advice on standardized diagnosis and treatment for spinal diseases during the coronavirus disease 2019 pandemic, " which suggested that chest computed tomography and SARS-CoV-2 nucleic acid test should be performed three days before surgery [3,6]. Patients with confirmed COVID-19 should be transferred to the isolation ward for further treatment.…”
Section: Management Principlesmentioning
confidence: 72%
See 1 more Smart Citation
“…The authors designed an algorithm to assess patients, presented in Fig.1. This is in contrast to the previous review, "Advice on standardized diagnosis and treatment for spinal diseases during the coronavirus disease 2019 pandemic, " which suggested that chest computed tomography and SARS-CoV-2 nucleic acid test should be performed three days before surgery [3,6]. Patients with confirmed COVID-19 should be transferred to the isolation ward for further treatment.…”
Section: Management Principlesmentioning
confidence: 72%
“…During the COVID-19 pandemic, it has been determined that all patients undergoing elective spine surgery should first receive COVID-19 screening to prevent nosocomial cross-infection. However, patients in emergency departments are more critical and serious, presenting with conditions including open fractures, multiple long bone fractures, and spinal fracture that require intermediate or emergency surgical intervention [3]. In this article, the authors describe their clinical practice guidelines for the management of COVID-19 in trauma patients with spine fractures.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, many adaptations in the health care structures are necessary with specific isolated rooms and operative theaters for COVID+ patients and the need for perfect coordination between all healthcare professionals [6,7]. According to Zou et al [5], the first step of management is related to screening for COVID-19 symptoms and triage of the patients that would require a surgical procedure. In our experience, we used systematic preoperative PCR-testing and reserved chest-CT-scan for suspected cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the entire series comprising 62 patients, only one tested COVID+ preoperatively and underwent surgery with the previously described protections measures [5].…”
Section: Surgical Datamentioning
confidence: 99%
“…Dear Editor, we read with great interest the article by Cesare Zoia, Daniele Bongetta, Pierlorenzo Veiceschi, Marco Cenzato, Francesco Di Meco, Davide Locatelli, Davide Boeris, and Marco M. Fontanella "Neurosurgery during the COVID-19 pandemic: update from Lombardy, northern Italy" [4]. This study provided important insights into the management of patients with the COVID-19 disease discovered in Wuhan [5] and the interpretation of these findings may be enhanced by the following considerations. In Italy since February 2020 spread a massive coronavirus disease (COVID-19) with a great number of infected patients and deaths.…”
mentioning
confidence: 99%